2015
DOI: 10.1002/advs.201500276
|View full text |Cite
|
Sign up to set email alerts
|

Graphene‐Nanowall‐Decorated Carbon Felt with Excellent Electrochemical Activity Toward VO2+/VO2+ Couple for All Vanadium Redox Flow Battery

Abstract: 3D graphene‐nanowall‐decorated carbon felts (CF) are synthesized via an in situ microwave plasma enhanced chemical vapor deposition method and used as positive electrode for vanadium redox flow battery (VRFB). The carbon fibers in CF are successfully wrapped by vertically grown graphene nanowalls, which not only increase the electrode specific area, but also expose a high density of sharp graphene edges with good catalytic activities to the vanadium ions. As a result, the VRFB with this novel electrode shows t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
107
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 169 publications
(108 citation statements)
references
References 55 publications
1
107
0
Order By: Relevance
“…Moreover, in the case of NCNTs@Ti foil, the values of ΔE p are 0.16, 0.13 and 0.19 V vs MSE when t 1 was set to 60, 90, and 120 s, respectively, while in the case of NCNTs@Ti mesh, the values of ΔE p are 0.28, 0.20, and 0.33 V vs MSE, demonstrating that the prepared electrodes provide good redox activity. These promising results are not only superior to those obtained with graphene-nanowallmodified carbon felt (lowest ΔE p = 0.339 V), [8] but also they are close to the best previously published results obtained on a carbon nanofiber/nanotube (CNF/CNT) composite catalysts grown on carbon felt (CNF/CNT-700, lowest ΔE p = 136.12 mV) as active electrode material in a VRFB. [25] A slight influence of the iron deposition time is observed with 90 s in both cases as shown in Figures 6 (a) and (b), providing the highest current densities and the lowest peak potential differences.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Moreover, in the case of NCNTs@Ti foil, the values of ΔE p are 0.16, 0.13 and 0.19 V vs MSE when t 1 was set to 60, 90, and 120 s, respectively, while in the case of NCNTs@Ti mesh, the values of ΔE p are 0.28, 0.20, and 0.33 V vs MSE, demonstrating that the prepared electrodes provide good redox activity. These promising results are not only superior to those obtained with graphene-nanowallmodified carbon felt (lowest ΔE p = 0.339 V), [8] but also they are close to the best previously published results obtained on a carbon nanofiber/nanotube (CNF/CNT) composite catalysts grown on carbon felt (CNF/CNT-700, lowest ΔE p = 136.12 mV) as active electrode material in a VRFB. [25] A slight influence of the iron deposition time is observed with 90 s in both cases as shown in Figures 6 (a) and (b), providing the highest current densities and the lowest peak potential differences.…”
Section: Resultssupporting
confidence: 88%
“…However, it was also shown that this standard electrode material (carbon felt/carbon nonwoven) has to be activated in order to provide an acceptable catalytic activity for vanadium ion redox conversion, and even in this case further improvement is desired to overcome kinetic limitations, as detailed above. Thus, recent research focusses on the investigation of catalytically active carbon material, such as carbon fibres, carbon nanotubes, mesoporous carbon, carbon nanospheres, and more.…”
Section: Introductionmentioning
confidence: 99%
“…[132] To fabricate practicable and recyclable electrodes with reduced cost, VAGNAs were prepared on carbon felt by PECVD (Figure 10b-d). [133] Compared with the original carbon felt, the VAGNAs-decorated carbon-felt exhibited much decreased charge transfer resistance. A three times higher reaction rate toward VO 2 + /VO 2+ redox couple, and an increase of energy efficiency by 11% over VRFB were achieved (Figure 10e,f).…”
Section: Vanadium Redox Flow Batteries (Vrfbs)mentioning
confidence: 99%
“…4 To enhance electrochemical activity and wettability of carbon based materials in VRBs, different surface modification methods have been used. Carbon electrodes have been coated with metals such as iridium, 5 doped with nitrogen 6 or decorated with nanomaterials such as graphene-nanowalls 7 or graphite carbon nanotubes. 8 Recently, Zhou et al reported activation of carbon papers and carbon cloth by heat-treatment and subsequent etching with KOH.…”
mentioning
confidence: 99%